ASSESSMENT OF THE INFLUENCE OF ELECTRONIC SCHOOL OF REPRODUCTIVE HEALTH ON THE STATE OF REPRODUCTIVE HEALTH OF ADOLESCENT GIRLS IN THE NOVOSIBIRSK REGION - Лукашева, Ольга Владимировна; Макаров, Константин Юрьевич; Борцов, Виктор Анатольевич; Кихтенко, Николай Андреевич (Mother and Baby in Kuzbass, 2023)
Objective. Тo assess the impact of an electronic reproductive health school on reproductive health indicators and reproductive behavior characteristics of teenage girls in the Novosibirsk region.Results. The characteristics of the control and observation groups upon re-application did not differ from each other. In the observation group, after using information from the electronic school of reproductive health, compared with the control group, there is a tendency towards an increase in the age of sexual debut, and a decrease in the number of teenage girls smoking.Significant statistical differences were revealed in the number of sexual partners: 2.16±0.37 in the control group versus 1.06±0.04 in the observation group upon re-treatment (p
Keywords: health of girls and teenage girls; reproductive health care; reproductive health; reproductive behavior; sex education; gynecological diseases